Effect of sacrificial piles on local scour around complex bridge piers - Mazen A. Elngar; Nahla M. AboulAtta; Neveen Y. Saad; Doaa A. El-Molla (Ain Shams Engineering Journal, 2024)
Sacrificial piles are used to minimize or remediate the local scour around existing bridge supports. This study evaluates the impact of using sacrificial piles on the scour around complex bridge piers. An experimental model is used to simulate nine different scenarios of sacrificial piles. Different numbers, arrangements, and distances of the sacrificial piles are studied. A large diameter sacrificial pile was also considered to evaluate the diameter’s effect. The results show that sacrificial piles are very effective in reducing scour around complex piers. An effective sacrificial piles arrangement should include an intermediate pile aligned with the center line of the complex pier. The scenario of three collinear piles in the transverse direction of the flow gave the best efficiency as it reduced the maximum scour depth by 63 % compared to the base case. On the other side, increasing the diameter of a single sacrificial pile enhanced its efficiency.